Integrating Dynamic Culture and Participatory Design in Urban Spaces for Sustainable Futures - Inès Sahtout; Imen Ben Youssef Zorgati; Zoubeir Lafhaj (Journal of Contemporary Urban Affairs, 2024)
This study explores the intersection of dynamic culture and participatory design in urban spaces, emphasizing the role of user experiences in shaping urban environments. By integrating residents' input in the design and planning processes, this research aims to foster sustainable, viable urban futures that reflect local cultural dynamics and community needs. Utilizing a case study in Tataouine, Tunisia, the research employs parametric mapping and user experience mapping to analyze interactions with heritage sites and public spaces. This approach captures qualitative data on user experiences and overlays it with spatial context, enabling the identification of patterns and relationships between cultural practices and territorial dynamics. The study aims to identify key factors for citizen participation, analyze user experiences in relation to cultural dynamics, and formulate recommendations for integrating participatory design principles. By aligning urban development with a dynamic culture and user-centric design, the study envisions urban spaces that are inclusive, sustainable, and reflective of local identities. The findings underscore the potential of participatory design to enhance the value of urban heritage and promote a more engaged and resilient urban community.